New media, new deontology: ethical constraints of online journalism - Mateus, Samuel (2020)
As New Media bring new challenges – as well as new risks – to the function and identity of journalism, there is a growing pressure to adopt – and also to adapt – self-regulatory mechanisms, such as deontological codes, in order to better determine the ethical boundaries of online journalism. This paper emphasizes key principles of New Media (such as hypermedia, hyperlinks, interactivity, glocality, customization, and instantaneity) that, together, pose legal, corporate, professional, and individual ethical constraints. Such limitations suggest a new deontology is needed for journalists to establish specific guidelines to direct their online practice. Finally, this article suggests that the first step towards a generalized ethical reassessment of online journalism could be accomplished by means of supranational deontological codes of journalism.